Prediction of the soil saturated paste extract salinity from extractable ions, cation exchange capacity, and anion exclusion - Visconti, Fernando; De-Paz, José M. (2017)
Process-based models could be used to predict the soil saturated extract salinity from extractable ion contents. However, a rigorous validation of such models for this purpose had not been carried out. A process-based model to predict the main inorganic ion composition, electrical conductivity, and pH of the saturated paste extract from extractable ion contents was developed step by step. The model development started from the principle of matter conservation in the soil solution as it concentrates from the 1 : 5 to the saturated paste extract. The need to include new hypotheses in the model was studied through calculation and analysis of standardised differences between measurements and model predictions. Therefore, best estimates of saturation paste extract properties occurred after taking into account the following: (i) free equilibration of the soil solution with the minerals calcite and gypsum under CO2 partial pressure of the saturated paste; (ii) further equilibration of the soil solution with the exchange complex; and (iii) determination of salt contents within the diffuse double layer (DDL) of the soil colloids, i.e. the anion exclusion. The last was necessary because the extracts where the determination of soil extractable anions (1 : 5 extracts), cations, and cation exchange capacity (CEC) were carried out were separated from their suspensions through centrifugation. Therefore, the reliable prediction of soil saturated paste extract salinity demands data on soil extractable ion contents, CEC, and the quantification of salts within the DDL.